82.5k views
4 votes
H(x)=2x-4/3
o h^-1(x)= 3x-12/2
o h^-1(x)= 3/(2x-4)
o h^-1(x)= 3x+4/2

User Joshua MN
by
5.1k points

2 Answers

5 votes

Answer:

D

Explanation:

Edg 2020

User Lucas Tierney
by
5.0k points
5 votes

Answer:


\large\boxed{h^(-1)(x)=(3x+4)/(2)}

Explanation:


h(x)=(2x-4)/(3)\to y=(2x-4)/(3)\\\\\text{Exchange x to y and vice versa}:\\\\x=(2y-4)/(3)\\\\\text{Solve for y:}\\\\(2y-4)/(3)=x\qquad\text{multiply both sides by 3}\\\\2y-4=3x\qquad\text{add 4 to both sides}\\\\2y=3x+4\qquad\text{divide both sides by 2}\\\\y=(3x+4)/(2)

User Espresso
by
5.0k points